METAL MATRIX COMPOSITE (MMC) DALAM PEMBENTUKAN LOGAM - Kuncara, Martina; Nana Nasuha, Cecep (Jurnal Ilmiah ATSAR Kuningan, 2025)
Metal Matrix Composites (MMC) are materials consisting of a metal mixture reinforced with continuous fibres, whiskers, or particulates.  Metal Matrix Composites (MMC) have advantages over other types of composites. Such as high strength, high modulus, high toughness and impact properties, low sensitivity to temperature changes or thermal shock, high surface resistance and low sensitivity to surface defects, and high electrical conductivity. The purpose of this review is to find out the methods used in manufacturing MMC, as well as the advantages and disadvantages of the method.  From the discussion, the results were obtained that various processing methods have been used in the manufacture of MMC, including Stir Casting methods, powder metallurgy, and Laser Additive Manufacturing (selective laser sintering (SLS), selective laser melting (SLM), laser metal deposition (LMD).